Increased reality: A new style of teaching in the chair of biology - Thalía Lucas Zambrano, Ana; María San Andrés Laz , Esthela (International Journal of Psychosocial Rehabilitation, 2020)
Information and communication technologies have complemented, enriched and transformed education. The potentialization of the educational process thanks to the great diversity of available resources becomes especially visible in the improvement of learning, Among these resources is augmented reality, a technology designed to simplify learning processes through the visualization and incorporation of virtual data into physical elements of reality, This form of connection between the world Real and digital content benefits learning by allowing its reinforcement through its association with reality. The objective of this research is to analyze the didactic advantages of augmented reality as a new teaching style in the Biology chair. Its development corresponds to qualitative research of a bibliographic type prepared from the review of primary information from specialized magazines that served to address the different categories of Augmented reality. The inductive method was used to infer from logical reasoning, and the conclusions Of the advantages offered by Biology teaching, the analytical method served to establish the benefits in relation to learning, motivation and academic performance. Among the conclusions, it was determined that the use of this technology applied to the subject area represents the opportunity to overcome traditional teaching methodologies and develop a new learning style.